Linking resource availability and heterogeneity to understorey species diversity through succession in boreal forest of Canada. (2nd October 2017) - Kumar, Praveen; Chen, Han Y. H.; Thomas, Sean C.; Shahi, Chander
Abstract: Understorey vegetation comprises the majority of species diversity and contributes greatly to ecosystem functioning in boreal forests. Although patterns of understorey abundance, species diversity and composition associated with forest stand development are well researched, mechanisms driving these patterns remain largely speculative. We sampled fire‐origin stands of varying stand ages and overstorey compositions on mesic sites of the boreal forest of Canada and used structural equation modelling (SEM) to link time since fire (stand age), light availability and heterogeneity, substrate heterogeneity and soil nitrogen to understorey vegetation cover and species diversity. The most parsimonious model for total understorey cover showed a positive direct effect of stand age ( r = .43) and an indirect effect via mean light level (0.18) and shrub cover (−0.11), with a positive total effect (0.50); the per cent broadleaf canopy had a direct negative effect (−0.22) and an indirect effect via shrub cover (−0.11). The model for total understorey species richness showed an indirect effect of stand age via mean light (0.24), light heterogeneity (0.10) and substrate heterogeneity (0.07), with a positive total effect (0.52); per cent broadleaf canopy had an indirect effect via light heterogeneity (0.09), and substrate heterogeneity (−0.10). Soil nitrogen did not significantly influence either understorey cover or species richness. The models for vascular plants followed similar trends to those for total understorey cover and species richness; however, there was an opposite indirect effect of light heterogeneity for both cover and species richness of non‐vascular plants. Shrub cover had positive direct and negative direct and indirect effects on both vascular and non‐vascular cover and species richness. Synthesis . Our findings indicate that understorey cover and species diversity are driven by time since disturbance, light availability as influenced by overstorey and shrub layers, but with important additional effects mediated by light and substrate heterogeneity. Non‐vascular understorey vegetation is more strongly determined by time since disturbance than vascular vegetation, and negatively affected by broadleaf tree abundance. The overall results highlight the importance of colonization, light availability and heterogeneity, substrate specialization and growth dynamics in determining successional patterns of boreal forest understorey vegetation. Abstract : Although patterns of understorey abundance, species diversity and composition associated with forest stand development are well researched, mechanisms driving these patterns remain largely speculative. Our findings highlight the conclusion that multiple mechanisms, including time since colonization, light availability and heterogeneity, and substrate heterogeneity determine patterns of understorey vegetation abundance and diversity through forest stand development following replacing disturbances.